2009
DOI: 10.3233/wor-2009-0886
|View full text |Cite
|
Sign up to set email alerts
|

Nonvocational outcomes of vocational rehabilitation: Reduction in health services utilization

Abstract: Background: Numerous studies have demonstrated the beneficial effects of vocational rehabilitation on vocational outcomes in individuals with a mental illness, yet effects on secondary outcomes remain largely unexplored. This study investigates the impact of vocational rehabilitation on the utilization of emergency, ambulatory care and inpatient services in individuals with a mental illness. Methods: Using a repeated measures study design, the utilization of health services by individuals with a mental illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Additional symptom and overall improvement of health equal to the results presented in the scoping review [32,46,47] were found in a study by Jackson et al (2009). Significantly less emergency department or ambulatory care visits as well as reduced hospital admissions were analyzed when comparing outcomes before and during training or subsequent employment in a social enterprise [69]. Resulting impacts on annual health care costs from the perspective of the public health care system were calculated comparing social firms with individuals registered in supported employment programs [75].…”
Section: Health-related Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional symptom and overall improvement of health equal to the results presented in the scoping review [32,46,47] were found in a study by Jackson et al (2009). Significantly less emergency department or ambulatory care visits as well as reduced hospital admissions were analyzed when comparing outcomes before and during training or subsequent employment in a social enterprise [69]. Resulting impacts on annual health care costs from the perspective of the public health care system were calculated comparing social firms with individuals registered in supported employment programs [75].…”
Section: Health-related Outcomesmentioning
confidence: 99%
“…A small body of research gained insight into health-related outcomes in longitudinal studies [69][70][71][72][73][74] and for specific target groups such as homeless youth or pregnant and postpartum women enrolled in methadone treatment [70][71][72][73][74]. Additional symptom and overall improvement of health equal to the results presented in the scoping review [32,46,47] were found in a study by Jackson et al (2009). Significantly less emergency department or ambulatory care visits as well as reduced hospital admissions were analyzed when comparing outcomes before and during training or subsequent employment in a social enterprise [69].…”
Section: Health-related Outcomesmentioning
confidence: 99%
“…While research into the health effects of SE has continued to grow over the last decade, there are some limitations identified within the existing body of literature. Only a small number of studies have used health-specific outcome measures to evaluate the health effects of SEs (Aklin et al , 2014; Ferguson and Xie, 2008; Gilbert et al , 2013; Jackson et al , 2009; Milton et al , 2015) and there are currently few SE studies that use repeat measures to track changes in participants’ health over time (Aklin et al , 2014; Ferguson and Xie, 2008; Jackson et al , 2009). Many studies focus on the perspectives of only one type of participant – for example, SE beneficiaries (Milton et al , 2015; Paluch et al , 2012) or SE managers and staff (Chan, 2015; Kidd et al , 2015; Roy et al , 2017).…”
Section: How Do Social Enterprises Impact Health? Evidence and Research Gapsmentioning
confidence: 99%
“…Others highlight the need to explore potentially negative experiences of SE participants (Farmer et al , 2016; Milton et al , 2015; Munoz et al , 2015). There are calls for studies that follow multiple types of outcomes for SE participants and communities – such as health and functioning (Gilbert et al , 2013), benefits to well-being (Ho and Chan, 2010), health service use, employment (Jackson et al , 2009) and social inclusion (Paluch et al , 2012). A systematic review by Roy et al (2014) highlights a particular gap regarding the causal mechanisms in SEs that impact on health and well-being, and others acknowledge the need to better understand how SEs contribute to outcomes such as employment, mental health, social participation (Lysaght et al ,2012), and economic mobility (Chan, 2015).…”
Section: How Do Social Enterprises Impact Health? Evidence and Research Gapsmentioning
confidence: 99%
“…There are also Canadian studies, including the aforementioned study by Quarter et al (2015a), that have also examined participant outcomes of supported social enterprises, including affirmative/alternative businesses. An Alberta study found that persons with psychiatric disabilities had fewer emergency department visits, ambulatory care visits, and hospital admissions, but no difference in hospital length of stay during the period that they were employed at a social enterprise as compared with pre-employment (Jackson, Kelland, Cosco, McNeil, & Reddon, 2009). In another Canadian study, researchers examined the transformation of sheltered workshops into supported social enterprises and the subsequent outcomes for workers with psychiatric disabilities (Krupa, Lagarde, & Carmichael, 2003).…”
Section: Introductionmentioning
confidence: 99%